Implementasi Business Intelligence Untuk Menganalisis Data Jumlah Penduduk Di DKI Jakarta Menggunakan Platform Tableau - Hibatullah Faisal; Faisal Parsakh Nursyamsi; Indra Ramadhan; Lingga; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
In Indonesia, especially in the province of DKI Jakarta, population growth continues to increase every year. Data regarding population growth in the province of DKI Jakarta is an important factor for consideration in decision making based on the visualization results on the data. The purpose of this article is to visualize population growth data from 2019 to 2021 in the province of DKI Jakarta by implementing a Business Intelligence system to display the results of the development of the number of population growth that has been recorded in 2019 to 2021 in the province of DKI Jakarta. The method is to process the population dataset in the DKI Jakarta province from www.data.jakarta.go.id using Tableau. The results are in the form of reports in the form of dashboards such as total population data, the number of population growth by year and city in the DKI Jakarta province which can be used to support a decision making. Display data generated from the results of the analysis will be visualized with an interactive dashboard with Tableau so that it is easy to understand.